Silicon Application to Several Soybean (Glycine max, Merrill) Varieties Under Drought Stress Condition - Yonny Koentjoro; F. Deru Dewanti; Sukendah; Djoko Purnomo; Edi Purwanto (Nusantara Science and Technology Proceedings, 2021)
Drought stress becomes a serious threat to the cultivation of soybean because it could affect the whole processes of soybean plants that may ultimately result in a significant reduction in yield. To obtain high production in drought stress conditions, one needs such efforts as including the use of utilizing high yielding varieties resistant to drought and/or designing environmental alteration engineering by using compounds or substances which can set osmolitic regulation. This study aims to determine the effect of the use of silicon (silica) on the four morpho-agronomic characters of soybean varieties tested. The study is designed by using a Factorial Randomized Block Design basis and implemented at the Faculty of Agriculture experiment station UPN “Veteran” Jawa Timur. The results showed that there were are significant interactions between treatment varieties and silica concentration for of the variables; the number of branches, number of pods per plant, and seed weight per plant. Character of each variety show varied responses to the application of silicon. Silicon concentration of 20 cc / l increased the weight of seed weight per plant and seed yield potential per hectare.